Drying kinetics and quality of dried kedondong fruits undergoing hybrid drying processes - Ee, Cheak Theng (2021)
Kedondong fruit (Spondias dulcis Forst.) is an underutilized fruit that is gaining interest in many countries (Malaysia, India, Australia, Philippines and etc) as it is nutritious and can be planted easily. Kedondong fruit is rich in total polyphenols, vitamin C, carotenoids and vitamin A which may prevent degenerative diseases such as cancer, arthritis, arteriosclerosis, heart disease, inflammation, brain dysfunction and ageing. The objectives of this study were to investigate the drying kinetics of hot air, infrared and hybrid drying (freeze drying + hot air drying (FDHA) and freeze drying + infrared drying (FDIR)). Besides, the effects of hot air, infrared and hybrid drying on physical characteristics (colour and texture), chemical characteristics (total polyphenols content, vitamin C and antioxidant capacity) and sensory evaluation were also studied. Kedondong slices were first dried using hot air drying at 50˚C, 60˚C, 70˚C and 80˚C and infrared drying at 60˚C, 70˚C and 80˚C to study the drying kinetics, physical and chemical characteristics of dried kedondong samples. Two falling rate periods were detected in hot air drying at higher temperature (60˚C, 70˚C and 80˚C) whereas constant rate and falling rate periods were observed only at 50˚C. However, there was only one falling rate period detected in infrared drying. Effective diffusivities (Deff) were obtained ranging from 8.56 x 10-10 m2/s to 1.88 x 10-9 m2/s and 1.30 x 10-9 m2/s to 1.96 x 10-9 m2/s as temperature increased for hot air and infrared drying, respectively. Activation energies (Ea) were determined for hot air and infrared drying at 25.28 kJ/mol and 20.13 kJ/mol, respectively. Both drying methods showed the lowest total colour change, lower hardness, higher total polyphenols content, vitamin C and antioxidant capacity at drying temperature of 60˚C and this temperature was selected for hybrid drying.